‘Nature’, Childhood, and The Anthropocene: evaluating the challenges for Education Studies - David Blundell (Educational Futures, 2017)
This paper responds to the call for reflection on the future of Education Studies by considering possible impacts of the relatively recent proposition that we are living in The Anthropocene. Many scholars from multiple disciplines concerned with climate change now consider that the impact of humankind on the Earth and its systems is so pervasive that humans have become a telluric force with discernible and irreversible geological effects. This leads them to suggest that conventional distinctions between natural and human or cultural worlds found in Enlightenment modernity are no longer tenable. The paper explores some possible challenges that this collapse of nature into culture and vice versa might have for working assumptions concerning the naturalness of ‘the child’ and normatively constructed Childhood as underpinning for the institutional practices of schooling and as template around which policy is frequently framed. It concludes by discussing possibilities to understand children and their lives as social actors enmeshed in complex social and material networks and so to recognise the plurality of childhoods as responses to human biological immaturity. By circumventing the presumed naturalness of childhood, the paper aims to contribute to debates about the future of schooling and its institutions as the dominant means by which we seek to educate.